2017
DOI: 10.1126/science.aam5678
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity increases with the strength of negative density dependence at the global scale

Abstract: Theory predicts that higher biodiversity in the tropics is maintained by specialized interactions among plants and their natural enemies that result in conspecific negative density dependence (CNDD). By using more than 3000 species and nearly 2.4 million trees across 24 forest plots worldwide, we show that global patterns in tree species diversity reflect not only stronger CNDD at tropical versus temperate latitudes but also a latitudinal shift in the relationship between CNDD and species abundance. CNDD was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
261
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 238 publications
(295 citation statements)
references
References 56 publications
24
261
3
Order By: Relevance
“…However, in contrast to recent studies reporting a latitudinal gradient in the strength of conspecific negative density dependence (CNDD) in eastern forests in the United States and across 24 forest plots worldwide (Johnson et al 2012, LaManna et al 2017, we found little evidence that CNDD and phylogenetic negative density dependence (PNDD) were more prevalent in diverse tropical forests compared to less diverse subtropical and temperate forests. The lack of latitudinal gradients may be due to the limited number of plots and their locations in different biogeographic realms.…”
Section: Variation Among Forest Sitescontrasting
confidence: 54%
“…However, in contrast to recent studies reporting a latitudinal gradient in the strength of conspecific negative density dependence (CNDD) in eastern forests in the United States and across 24 forest plots worldwide (Johnson et al 2012, LaManna et al 2017, we found little evidence that CNDD and phylogenetic negative density dependence (PNDD) were more prevalent in diverse tropical forests compared to less diverse subtropical and temperate forests. The lack of latitudinal gradients may be due to the limited number of plots and their locations in different biogeographic realms.…”
Section: Variation Among Forest Sitescontrasting
confidence: 54%
“…Although supporting evidence is not unequivocal (Terborgh 2015, Ellwood et al 2016, Gainsbury and Meiri 2017, LaManna et al 2017), local dynamics in the tropics could exclude different consumers in different habitat patches, resulting in more specialized and less similar consumer communities across patches. Our results show that consumers segregated their dietary niches more in more constant environments (less consumer overlap) (Figure 3).…”
Section: Discussionmentioning
confidence: 98%
“…In the long run, these ecological processes result in the selection of numerous adaptive plant traits (Reich et al, 2003), allowing species to thrive in complex and highly diverse systems, such as Amazonian forests. The high diversity of tropical ecosystems is in part maintained by natural disturbances and local biotic interactions, sometimes promoted by herbivores and pathogens that reduce the abundance of the most effective competitors, creating space for other species (Connell, 1978;LaManna et al, 2017).…”
Section: Introductionmentioning
confidence: 99%